Psychological Dynamics of Individual with Acute and Transitional Psychotic Disorders - Permatasari, Dyah; Vrisaba, Nanda Audia (Proceedings of The International Conference on Psychology and Education, 2024)
Acute-Transient Psychotic Disorder is a mental condition in which individuals have difficulty understanding or assessing reality, often characterized by symptoms such as delusions, hallucinations, strange behavior, and disorganized speech. Based on the DSM-V, this disorder differs from schizophrenia mainly in duration, which occurs within 1 day to less than 1 month. This study aims to determine and understand the psychological picture of individuals who have acute and transient psychotic disorders. The researchers uses a single case study method with a qualitative approach. In the examination process, the researchers collects data by conducting interviews, observations, and looking at the subject's medical records. The results show that acute and transient psychotic disorders can occur due to internal and external factors from the subject. This can also be studied more deeply using Freud's psychoanalytic approach related to defense mechanisms and psychosexual development.